(untitled) (Jurnal Bahasa, 2006)
Popular fiction written in Malay is often construed by Malay literary scholars as marginalized literature and have very little literary value. Novels published by Alaf 21 which fall within this category have how-ever been able to capture the interest of readers of Malay novels. This is reflected in the sale of the novels which have chalked up thousands of copies. The overwhelming response to these novels makes for an interesting object of study. The common theme of these novels is love in a troubled marriage and they are mostly written by women. The depiction of "strong" women will be the focus of this paper. Insyirah is saddled with a jealous husband; Najmah, who is in a polygamous marriage, is trapped with a possessive husband; and Farah, who mar-ried her former brother-in-law, is also trapped with a brother-in-law/ husband who is egoistic. The conflicts and challenges that these women face and how they rise above them will be discussed from a linguistic approach. The word kuat / strong is analyzed through cognitive semantic’s radial category networks and its extended meanings as manifested in words like kukuh/firm, tabah/brave, tidak gentar/not afraid and etc. These words are used in the depictions of these women. Novels are usually assumed to be the subject of literary studies, how-ever, in this paper the novels chosen have become the corpus of a linguistic study by applying a linguistic theory in the analysis.